Social Dynamics: Does it Have an Impact on the Existence of Education? - Bintang R. Simbolon; Teguh Setiawan Wibowo; Ujang Suherman (ijd-demos, 2022)
AbstractThe purpose of this study was to analyze the influence of social dynamics on the existence of education. This study uses a qualitative-descriptive type of research. This research will focus its attention on various actual problems in the field. Based on the results of data analysis, it can be concluded that n terms of the times, especially on the development and advancement of technology, there are many impacts and influences on our education, both positive and negative. We need to be wise in utilizing every positive effect that arises to follow developments and make our education even better but still supported by appropriate and adequate facilities and infrastructure. Then for the negative impact, we must be able to do our best to minimize every adverse effect so that our nation is eroded by the times, our education is not left behind, and the future generations of our country can answer and face every challenge and obstacle of the times that arise in our social life.Keywords: social dynamics, education, impact. AbstrakTujuan penelitian ini adalah untuk menganalisis pengaruh dinamika sosial terhadap eksistensi pendidikan. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif. Penelitian ini akan memfokuskan perhatiannya pada berbagai permasalahan aktual di lapangan. Berdasarkan hasil analisis data dapat disimpulkan bahwa dari segi perkembangan zaman khususnya perkembangan dan kemajuan teknologi, banyak sekali dampak dan pengaruhnya terhadap dunia pendidikan kita, baik positif maupun negatif. Kita perlu bijak dalam memanfaatkan setiap dampak positif yang muncul untuk mengikuti perkembangan dan menjadikan pendidikan kita lebih baik lagi namun tetap didukung oleh sarana dan prasarana yang memadai dan memadai. Kemudian untuk dampak negatifnya, kita harus bisa berusaha semaksimal mungkin untuk meminimalisir setiap dampak buruk agar bangsa kita tergerus zaman, pendidikan kita tidak ketinggalan, dan generasi penerus bangsa kita bisa menjawab dan menghadapi setiap tantangan dan kendala zaman yang muncul dalam kehidupan sosial kita.Kata kunci: dinamika sosial, pendidikan, dampak